#TITLE_ALTERNATIVE# - HUTAGALUNG, GASTON
Ultrafiltration is an efficient and selective, pressure driven process for the sparation of solutes by permeation through a semipermeable membrane. Solutes, colloids or particles of dimensions larger than the molecular weight cut off of the membrane are retained in the solutions, while solutes smaller than the pores pass with the solvent through the membrane substructure. Different polysulfone (PSf) assymetric membrane of varying PSf concentrations were prepared for the clarification of molasses using ultrafiltration techniques. Preparation of the membrane were conducted by mixing dimethylacetamide (DMAc) with PSf to give final concentrations of PSf -DMAc w/w of 15.5, 16.0, 16.5, 16.75, and 17.5 %. The mixtures were homogenized as thin films of certain thickness on glass plate which were then immersed in water. Water fluxes through 15.5, 16.0, 16.5, 16.75, and 17.5 % polysulfone membranes at the steady state were 227.48, 148.15, 11+0.63, 92.83, and 11.60 l.m-2.h-1 respectively. Determination of rejection coefficient for PSf 16.5 and PSf 16.75 towards dextran T40 were 56.3 and 75.9 %, and towards dextran T70 were 71.6 and 78.4 % respectively. The molecular weight cut off of PSf 16.75 was 500,000. The basic process of determination of water fluxes and rejection coefficient were identical with solutions of dextran T40, T70, and T500 substituting water in the determination of rejection coefficient and molecular weight cut off of the membrane. A stirred cell was used. Application of the prepared membrane in the clarification of molasses after characterization of their effectiveness and selectivity showed that PSf 16.75 could clarify molasses effectively with a rejection coefficient of 23.5-26.2 % for colouring matters and 29.1-35.4 % for glucose. The ability to separate solts from the molasses reached a value of more than 60 %. Filtering of the permeate from ultrafiltration of molasses using Whatmann No.1 filter paper showed that clarification of molasses using PSf membranes was equally or more effective than filtering through filter papers.